Efeito da posição prona na diurese e balanço hídrico de pacientes pediátricos submetidos a ventilação mecânica - Dall'Agnese, Rosirene Maria Fröhlich (2017)
Introduction: Respiratory diseases in pediatrics are important causes of hospitalization in the Pediatric Intensive Care Unit (PICU) and, not withstanding, to the need for mechanical ventilation. The use of mechanical ventilation and continuous sedation associated with the administration of fluids, which severe patients need for initial hemodynamic stabilization, often result in a cumulative positive fluid balance. This hydric overload is associated with worse outcomes. Among the alternatives for the hydric balance to be optimized, the establishment of the prone position is found as such. Objectives: To verify if the prone position in pediatric patients submitted to mechanical ventilation increases diuresis with optimization in the hydric balance as well as to verify if this improvement has repercussions in days of mechanical ventilation and hospitalization in PICUs. Methods: Retrospective cohort through review of medical records. It was selected patients who were submitted to ventilation for pulmonary causes and aged from 1 month old to 12 years old. The prone group (PG) was the one in which the patients were submitted to the prone position at some point of the study. The control group (CG) was the one in which the patients met the inclusion criteria but were not undergone prone position. The collected data included demographic data, Pediatric Index of Mortality (PIM 2), hydric balance, diuresis, use of diuretics and vasoactive drug index, mechanical ventilation duration, prone position duration, relationship between prone and mechanical ventilation duration, besides duration of hospital stay (PICU and hospital). Mann-Whitney and Chi-Square tests were used to compare the PG and CG groups. For the longitudinal analysis, repeated measures of ANOVA were used, using BH (ml/kg/day), diuresis (ml/kg/h) and the amount of furosemide (mg/kg/day) during a period classified as D1 to D4 (D1 being the first day of mechanical ventilation in the CG and the day immediately before prone in the PG). The main outcome was the increase of diuresis and the improvement of hydric balance in pronated patients. The secondary outcome was the decrease of duration of mechanical ventilation and hospitalization in the PICU and in the hospital. Results: 84 patients were included and, after some losses, 77 (PG=37 and CG=40) remained. Regarding age, sex, pathologies, index of mortality, death, use of vasoactive drugs and occurrence of intercurrences, the groups were similar. There was no significant improvement of diuresis, hydric balance, mechanical ventilation and hospitalization duration in the PICU. Regarding the use of diuretics, there was greater use of furosemide (P<0.001) and spironolactone (P=0.04) in the PG. When performed a longitudinal analysis of repeated measures of D1 to D4, it was shown that both PG and CG had improved diuresis and hydric balance, with a more significant improvement from D1 to D2 in the PG (P=0.034). However, when verifying this improvement, it was noticed that it was also related to the use of diuretics. Conclusion: Throughout the analysed days of mechanical ventilation (D1 to D4), there was improvement of both diuresis and hydric balance of patients in both groups, without showing, however, superiority of the prone group in relation to the control group.